METAL LEVELS OF MACROALGAE FROM ISKENDERUN AND MERSIN BAY TURKEY EASTERN MEDITERRANEAN - Erguden, Sibel Alagoz; Erguden, Deniz; Ciftci, Nuray; Akbora, Hasan Deniz; Ayas, Deniz (Parlar Scientific Publications (P S P), 2021)
This study aimed to determine metals' concentrations (Cr, Se, Fe, Cu, Zn, Cd, V, As, Sr, Pb) in macroalgae species sampled from Iskenderun and Mersin Bay between June -October 2018, and these samples were from the depths of 0 to 2 meters. Inductively coupled plasma mass spectrometer (ICP-MS) technique was used for metal analysis. Differences in the metal levels were analyzed using the ANOVA method. Metal concentrations of samples were found as Fe> Sr> Zn> Cr> Cu> V> Se > As> Pb> Cd and Fe> Sr> Zn> Cr> Pb> Cu> V> Se> As> Cd from Iskenderun Bay and Mersin Bay, respectively (p <0.05). In terms of metal levels, the only distinction between the sites was that the average Pb level. In Mersin Bay, it was higher (p<0.05). The results show that Fe and Sr were detected at high levels in both bays. The species with the highest Fe levels were Ulva lactuca from Iskenderun and Enteromorpha prolifera from Mersin Bay. The highest Sr levels were observed in Padina pavonica in both bays. Among other metals, Cu and Zn, which are essential for macroalgae, seem relatively low.
Keywords: Marine macroalgae; metal accumulation; bio-indicators; Eastern Mediterranean Sea